Dancing and Singing Steel: Zora Neale Hurston in Chicago. Issue 3 (2nd September 2022) - Weir, Rebecca Nicholson
ABSTRACT: This article discusses Zora Neale Hurston's 1934 Chicago based dance concert titled Singing Steel, which was set in a Florida railroad worker camp and based on songs and dances collected during her ethnographic research. A close reading of the archival records of her months spent in Chicago reveal a turning point in Hurston's life, a moment where she utilized the social and commercial networks and opportunities in the city to think about what she wanted to do next and where she wanted to go with her career. Hurston's time in Chicago, rehearsing and promoting Singing Steel worked to simultaneously showcase African American dance and music as sophisticated artforms and commercially successful fundraising entertainment. Chicago served as a crossroads in which she made crucial decisions for her future work as a choreographer, anthropologist, and writer. Expanding the timeline of Hurston's autumn in Chicago producing and directing Singing Steel extends the understanding of Hurston's impact on Chicago's African American, literary, musical, and dance communities and their lasting impact on her.